Jus Buah Bit Campur Jeruk Nipis untuk Menurunkan Hipertensi pada Ibu Perimenopause - Lesta Ningrum Aprilia; Susilawati Susilawati; Neneng Siti Latifah; Samino Samino (Calory Journal Medical Laboratory Journal, 2024)
Hypertension is one of the diseases that perimenopausal mothers are susceptible to. Based on data at the Rajabasa Indah Community Health Center in 2022, the number of elderly hypertensive sufferers undergoing examination was 1050 people, this number has increased compared to 2021, which was 989 people and 2020, which was 793 people. The cause of high levels of hypertension is the lack of public attention to the importance of regular health checks. One effort to reduce hypertension is to give beet juice mixed with lime which contains nitrates and potassium which can reduce hypertension. The aim of the research was to determine the effect of beetroot juice mixed with lime on reducing hypertension in perimenopausal mothers at the elderly posyandu in Rajabasa Village, Bandar Lampung in 2024. Quantitative research type, one group pretest-posttest design. The population of this study was all perimenopausal mothers who experienced hypertension who were registered at the Posyandu for the Elderly, Rajabasa Village, Bandar Lampung, totaling 50 respondents. The sample for this research was 33 respondents. 250ml/day of beetroot juice mixed with lime was given for 7 consecutive days. Data collection used observation sheets, univariate and bivariate data analysis (paired sample t-test).Based on the research results, it is known that the average systolic blood pressure of perimenopausal mothers before being given beet juice mixed with lime was 158.15mmHg with a standard deviation value of 9.111mmHg, a minimum value of 145mmHg and a maximum value of 178mmHg, while the average systolic blood pressure of perimenopausal mothers after being given beetroot juice mixed with lime is 125.91mmHg with a standard deviation value of 8.064mmHg, a minimum value of 110mmHg and a maximum value of 141mmHg with a p-value of 0.000. And it is known that the average diastolic blood pressure of perimenopausal mothers before being given beetroot juice mixed with lime was 99.21mmHg with a standard deviation value of 4.477mmHg, a minimum value of 87mmHg and a maximum value of 105mmHg, while the average diastolic blood pressure after being given mixed beetroot juice lime is 83.03mmHg with a standard deviation value of 5.725mmHg, a minimum value of 74mmHg and a maximum value of 94mmHg with a p-value of 0.000. There is an effect of giving beetroot juice mixed with lime on reducing hypertension in perimenopausal mothers at the elderly posyandu, Rajabasa Village, Bandar Lampung in 2024